STANDARDIZATION OF LIMITED STAY ONLINE LICENSE SERVICE FOR FOREIGN WORKERS IN INDONESIA - Moch Iqbal Masrur Rahma; Agung Sulistyo Purnomo (Jurnal Ilmiah Kajian Keimigrasian, 2019)
Presidential Regulation Number 20 of 2018 on the Use of Foreign Workers mandates new administrative duties for Immigration Agency in terms of granting residence visas and permits for Foreign workers. The online single submission, is an application in which integrates the system of the Directorate General of Immigration and the Ministry of Manpower. It is expected that the administrative procedure for foreign workers in entering Indonesian will be less complicated than before in order to boost national economic growth in the Unitary State of the Republic of Indonesia. For this reason, the study aims to figure out a standard of public service in Immigration Clearance for Foreign Workers at Immigration Checkpoints. This study uses an empirical-normative approach that examines the Immigration Clearence procedure for Foreign Worker after the enactment of Presidential Regulation Number 20 of 2018 concerning the Use of Labor. This research begins with library and field research. The data collection techniques used in this study are observation, interviews, and documentation. Furthermore, to analyse the system of Immigration clearance of foreign worker at Immigration Checkpoint, I will utilise the public service standard from The act number 25 of to 2009 about public services. The result of the study indicates that the implementation of Online Single Submission hasn’t been fully met the ideal public service standards.